Global Evidence on the Determinants of Public Trust in Governments during the COVID-19 - Giray Gozgor (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Using the Worldwide COVID-19 Attitudes and Beliefs dataset covering 108,918 respondents from 178 countries, the paper examines the determinants of public trust in governments during the COVID-19. It is found that older and healthy people trust more to their governments. Education is negatively related to trust in governments. The results are robust to consider different measures of trust in government as well as including various controls, such as precautionary behaviors, first-order beliefs, second-order beliefs, and the COVID-19 prevalence in the country. The findings are also valid for countries at different stages of economic development as well to varying levels of globalization, institutional quality, and freedom of the press.
Keywords: I18; D81; C31; C83; 330; the COVID-19 pandemic; trust in governments; global survey data; economic development; institutional quality; freedom of the press